Data integration for environmental mapping and monitoring in South Tyrol - Lemenkova Polina (Western Balkan Journal of Agricultural Economics and Rural Development)
This study has presented the estimate of the catchment-level water balance by assessing components separately using different field methods of a subalpine forest in South Tyrol region (north Italy). The techniques of geospatial analysis, statistical modelling and mapping were used for analysis of environmental and hydrological variables in coniferous forest. Methods - tools included data integration, processing and modelling. Techniques employed eddy covariance (EC) of tree transpiration sensors, phenocam images, throughfall and stemflow gauge. These instruments were employed to measure water discharge, soil humidity, and quantify moisture in epiphytes. After data collection, the data were modelling using Python-based statistical libraries. The aim was to monitor a dense old (>200 years old) and young (<30 years old) forests in different seasons (wet and dry periods) in order to compare their effect on water balance. The study is located in South Tyrol. The cumulative effects of climate and environmental change were quantified by environmental habitat assessment. The resistance of young and old forests to climate effects was analyzed on landscape level. Environmental monitoring is a key tool for understanding the climate challenges in forest ecosystems. The results revealed that the age of trees and availability of lichens on the trunks contribute to water balance through increased humidity and interception of water by canopy. This study contributes to environmental analysis of climate-hydrological dynamics of mountain habitats in North Italy.